Challenges Facing Maine's Budget Process - Nicoll, Donald (Maine Policy Review, 1993)
The budget difficulties faced by Maine and by most other states have prompted a national search for better ways to deliver government services. In Maine, a conference entitled "Rethinking Maine Government" was held at the University of Maine on January 5-6, 1993 under the auspices of the Margaret Chase Smith Center for Public Policy. Maine Policy Review selected three of the presentations at that conference for this issue. Donald Nicoll was the co-chair, along with Merton Henry, of the Special Commission on Governmental Restructuring.
Keywords: Maine state budget; government restructuring